Pelaksanaan Pemasangan Alat Kontrasepsi IUD dan Inplant Gratis di Klinik Nirmala Medan Tahun 2022 - Kamaliah Kamaliah; Fatwiany Fatwiany; Elvi Sepriani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The family planning program is an effort to increase public awareness and participation through maturation of marriage age, birth control, fostering family resilience, and improving family welfare in order to realize a small, happy and prosperous family. IUD (Intra Uterine Device) is a plastic contraceptive that has a shape like the letter